2018
DOI: 10.3899/jrheum.180104
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegaloviral or Pneumocystis Jiroveci Pneumonia Increases Mortality in Systemic Lupus Erythematosus Patients with Pulmonary Hemorrhage: Evidence from Bronchoalveolar Lavage Fluid

Abstract: Objective.To evaluate the role of cytomegaloviral or Pneumocystis jiroveci pneumonia (CMV/PJP) in systemic lupus erythematosus (SLE) patients with pulmonary hemorrhage (PH).Methods.We retrospectively examined hospital records for 27 SLE patients with PH who received bronchoalveolar lavage fluid (BALF) analyses. Clinical profile and mortality rates were compared between groups with and without CMV/PJP. Risk factors for PH-related mortality were analyzed.Results.Among 27 SLE patients with PH, 15 had pathogens fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our study found that CMV co‐infection was more common in patients with PJP than in the non‐PJP patients, which is consistent with previous studies 30 . Some researchers have suggested that CMV impairs the host immune response to P. jirovecii , resulting in delayed clearance and worse clinical outcomes 31–35 . Currently, limited methods are available for the detection of CMV and other viruses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that CMV co‐infection was more common in patients with PJP than in the non‐PJP patients, which is consistent with previous studies 30 . Some researchers have suggested that CMV impairs the host immune response to P. jirovecii , resulting in delayed clearance and worse clinical outcomes 31–35 . Currently, limited methods are available for the detection of CMV and other viruses.…”
Section: Discussionsupporting
confidence: 91%
“…30 Some researchers have suggested that CMV impairs the host immune response to P. jirovecii, resulting in delayed clearance and worse clinical outcomes. [31][32][33][34][35] Currently, limited methods are available for the detection of CMV and other viruses. However, mNGS can detect almost all viruses, and should be considered for use in CTD patients to improve PJP and CMV detection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids inhibit the activation, proliferation, differentiation and survival of macrophages, T lymphocytes and other inflammatory cells, and they promote T cell apoptosis [ 18 ]. Long-term application of the above therapies reduces the clearance capacity of fungi and bacteria, and it increases the risk of infection [ 5 , 19 ]. SLE activity leads to a vicious cycle in which immunosuppressants are difficult to reduce or SLE recurs and immunosuppressants have to be increased again.…”
Section: Discussionmentioning
confidence: 99%